RNA interference gene therapy in dominant retinitis pigmentosa and cone-rod dystrophy mouse models caused by GCAP1 mutations - Jiang, Li; Frederick, Jeanne M.; Baehr, Wolfgang (Frontiers in Molecular Neuroscience, 2014)
RNA interference (RNAi) knockdown is an efficacious therapeutic strategy for silencing genes causative for dominant retinal dystrophies. To test this, we used self-complementary (sc) AAV2/8 vector to develop an RNAi-based therapy in two dominant retinal degeneration mouse models. The allele-specific model expresses transgenic bovine GCAP1(Y99C) establishing a rapid RP-like phenotype, whereas the nonallele-specific model expresses mouse GCAP1(L151F) producing a slowly progressing cone/rod dystrophy (CORD). The late onset GCAP1(L151F)-CORD mimics the dystrophy observed in human GCAP1-CORD patients. Subretinal injection of scAAV2/8 carrying shRNA expression cassettes specific for bovine or mouse GCAP1 showed strong expression at one week post-injection. In both allele-specific (GCAP1(Y99C)-RP) and nonallele-specific (GCAP1(L151F)-CORD) models of dominant retinal dystrophy, RNAi-mediated gene silencing enhanced photoreceptor survival, delayed onset of degeneration and improved visual function. Such results provide a “proof of concept” toward effective RNAi-based gene therapy mediated by scAAV2/8 for dominant retinal disease based on GCAP1 mutation. Further, nonallele-specific RNAi knockdown of GCAP1 may prove generally applicable toward the rescue of any human GCAP1-based dominant cone-rod dystrophy.